2017
DOI: 10.1053/j.seminhematol.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1 deficiency (familial platelet disorder with predisposition to myeloid leukemia, FPDMM)

Abstract: In this review, we discuss disease-causing alterations of RUNT-related transcription factor 1 (RUNX1), a master regulator of hematopoietic differentiation. Familial platelet disorder with predisposition to myeloid leukemia (FPDMM) typically present with 1) mild to moderate thrombocytopenia with normal-sized platelets; 2) functional platelets defects leading to prolonged bleeding; and 3) an increased risk to develop MDS, AML or T-ALL.Hematological neoplasms in carriers of a germline RUNX1 mutation need addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 68 publications
1
52
0
1
Order By: Relevance
“…Studies have linked germline mutations in GATA2 , RUNX1 , ETV6 and DDX41, among other selected genes, with a predisposition to MDS and AML (Bannon & DiNardo, ; Sperling et al , ). RUNX1 germline mutations have been associated with FPDMM with a median age of onset of MDS/AML of 33 years (Owen et al , ; Schlegelberger & Heller, ). Patients with germline GATA2 haploinsufficency have a 50% risk of MDS/AML and often present with unilineage cytopenia, nontuberculous mycobacterial and viral infections, and monosomy 7 or trisomy 8 karyotypic abnormalities (Babushok et al , ).…”
Section: Role Of Ngs In Mds Diagnosismentioning
confidence: 99%
“…Studies have linked germline mutations in GATA2 , RUNX1 , ETV6 and DDX41, among other selected genes, with a predisposition to MDS and AML (Bannon & DiNardo, ; Sperling et al , ). RUNX1 germline mutations have been associated with FPDMM with a median age of onset of MDS/AML of 33 years (Owen et al , ; Schlegelberger & Heller, ). Patients with germline GATA2 haploinsufficency have a 50% risk of MDS/AML and often present with unilineage cytopenia, nontuberculous mycobacterial and viral infections, and monosomy 7 or trisomy 8 karyotypic abnormalities (Babushok et al , ).…”
Section: Role Of Ngs In Mds Diagnosismentioning
confidence: 99%
“…The mean platelet volume by automated method and platelet size on microscopic examination is normal. On the May‐Grunwald‐Giemsa stained peripheral blood smear examination, platelets reveal normal morphology or may have a gray appearance due to reduction in alpha granules. In a study by Kanagal‐Shamanna et al peripheral blood smears in a subset of FPD/AML patients with myeloid neoplasm revealed mild platelet anisocytosis and abnormalities in platelet granulation, namely hypo‐ or agranulation, along with red cell macrocytosis and cytoplasmic hypogranulation and abnormal nuclear segmentation in granulocytes.…”
Section: Myeloid Neoplasms With Germline Runx1 Mutationmentioning
confidence: 99%
“…Dysmorphic megakaryocytes are a consistent finding (Figure 1), present even prior to MDS or leukemic transformation and accounting for more than 10% of the megakaryocytes in the majority of cases. 40,41 Small forms with scant cytoplasm and nuclear hypolobation, with asynchronous nuclear-cytoplasmic maturation and micromegakaryocytes, are common 40,42 in the absence of MDS/AML. Bone marrow eosinophilia has been frequently noted.…”
Section: Bone Marrowmentioning
confidence: 99%
“…In addition, genetic anticipation in families with RUNX1 germline pathogenic variants has been reported; thus, family members should be counseled and closely monitored after the diagnosis of an RUNX1 mutation in a patient. 26 Schlegelberger and Heller 26 recommend regular clinical examinations including a complete blood count (CBC) with differential and a yearly bone marrow examination, with counseling regarding the signs and symptoms of leukemia.…”
Section: Runx1 and Familial Platelet Disordermentioning
confidence: 99%